Kompensasi, Persepsi Mutasi Ke Luar Jawa dan Motivasi Kerja Prajurit TNI Angkatan Laut - ., Suhardi; Matulessy, Andik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
This study aims to examine the influence of compensation and perception mutations outside Java with motivation to work with the subject as much as 100 soldiers Navy cadet who was penjalankan education in puslatdiksarmil Kobangdikal. This study use two independent variables (X), namely Compensation (X1) and perception mutations out of Java (X2). While the dependent variable (Y) is the work motivation. Based on regression analysis found the value of F regression = 16 201 with p = 0.000 (p <0.01), R squared of 0.250, meaning there was a significant relationship between compensation and perception mutations with Navy personnel Work Motivation, Compensation and perception mutations together -Same can be used as predictors of motivation to work, these two variables contribute effectively amounted to 25.04%. The value of r (correlation Partial) = 0.377, t = 4,004, with Sig / p = 0.000 (p <0.05), showed no correlation with the Compensation work motivation. Also found value of r (correlation Partial) = 0.292, t = 3,005, with Sig / p = 0.003 (p <0.05), suggesting perceptions of mutation also correlated significantly with the motivation to work, so the perception of single mutation can also be a predictor ride -turunnya work motivation Navy personnelKeywords : compensation, mutations perception, working motivation